Expression Level of Small Envelope Protein in Addition to Sequence Divergence inside Its Major Hydrophilic Region Contributes to More Efficient Surface Antigen Secretion by Hepatitis B Virus Subgenotype D2 than Subgenotype A2 - Qianru Wang; Shuwen Fu; Jing Zhang; Quan Yuan; Jisu Li; Ningshao Xia; Yu-Mei Wen; Yongxiang Wang; Shuping Tong (Viruses, 2020)
Hepatitis B surface antigen (HBsAg) promotes persistent hepatitis B virus (HBV) infection. It primarily corresponds to small (S) envelope protein secreted as subviral particles. We previously found that genotype D clones expressed less S protein than genotype A clones but showed higher extracellular/intracellular ratio of HBsAg suggesting more efficient secretion. The current study aimed to characterize the underlying mechanism(s) by comparing a subgenotype A2 clone (geno5.4) with a subgenotype D2 clone (geno1.2). Five types of full-length or subgenomic constructs were transfected to Huh7 cells at different dosage. HBsAg was quantified by enzyme linked immunosorbent assay while envelope proteins were detected by Western blot. We found that ratio of extracellular/intracellular HBsAg decreased at increasing amounts of DNA transfected. Conflicting findings from two types of subgenomic construct confirmed stronger secretion inhibitory effect of the genotype D-derived large envelope protein. Chimeric constructs followed by site-directed mutagenesis revealed geno1.2 specific V118/T127 and F161/A168 in the S protein as promoting and inhibitory of HBsAg secretion, respectively. In conclusion, more efficient HBsAg secretion by subgenotype D2 than subgenotype A2 is attributed to lower level of S protein expression in addition to V118 and T127 in S protein, although its F161 and A168 sequences rather reduce HBsAg secretion.